The Effect of Ammonium Sulfate Concentrations on The Size Distributions of NPK-Fertilizer Granules in a Rotating Drum Granulator - Hardhianti, Meiga Putri Wahyu; Sebastian, Ivan; Wiratni (Eksergi, 2025)
The granulation process is important in pharmaceuticals, detergents, and fertilizers. It consists of enlarging the particle size to create granules with specific properties. This study examined the wet granulation process for NPK fertilizers and investigated the effect of binder solutions, particularly ammonium sulfate (ZA) concentrations, on the distribution of granule sizes. The granulation process was conducted in a rotating drum granulator with varied NPK ratios (28-6-6, 20-20-8, 18-16-20, and 15-15-15) with amounts of binder (10 ml or 20 ml of 15% ZA solution or pure water). Granule sizes were analyzed using Image Pro Plus software, and Stoke’s number was calculated to establish a correlation between the average granule radius and Stoke’s number. The results showed that ammonium sulfate improved granulation, leading to larger granule size and more consistent size distribution in various NPK formulations than water-bond granules. Furthermore, a higher liquid-to-solid ratio generally increases granule size, resulting in a broader size distribution. The study demonstrated a robust correlation (R² = 0.95) between Stoke's number and the average granule radius, indicating that Stoke's number served as a generalized parameter of the granulation process for various NPK formulations and binder types.